WORKSHOP PENGARUH TEPUNG PISANG AMBON (Musa Paradisiaca) SEBAGAI MEDIA ALTERNATIF PERTUMBUHAN JAMUR Aspergillus flavus PENGGANTI MEDIA PDA (Potato Dextrose Agar) - Siregar, Sa’adah; Rizky, Vincentia Ade (MAJU : Indonesian Journal of Community Empowerment, 2025)
Fungi play a lot in the life both fungi that are saprophytic and are pathogenic, one that is pathogenisc and produce aflatoxin, the fungus Aspergillus flavus. PDA (Potato Dextrose Agar) is a medium commonly use for fungal growth. PDA medium are usually in the form instan so this media is ready to use. The composition of the PDA, one of which is a potato extract as a source of carbohydrates, so that other subtitutes can be carried out whose composition is almost the same as potatoes, using Ambon banana. Objective: The purpose of this research was to knew the comparison of Aspergillus flavus fungus diameter growth on PDA media and alternatif medium from ambon banana on concentration of 2%, 4% and 6%. Method: The methods this type of research was experimented by way of inoculating Aspergillus flavus with single dot method. Alternative media for ambon banana be used for the growth of the Aspergillus flavus fungus. Result: Data analysis by calculating the growth in the number of colonies growing at each contration shows that there are 85 colonies at a contration of 2%, 133 contration of 4%, and 130 contrations of 6% and there is a paired T-test abtained average results on ambon banana media with successive contrations of 2%, 4%, and 6% namely 77,33, 91,67, 123,33 and on the PDA (Potato Dextrose Agar) control media 92,33.